Influence of information communicative technologies on students' sport-oriented physical education interest - Oleg Olkhovy; Volodymyr Temchenko; Yuriy Petrenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: determination the influence of information communicative technologies on students' interest in regular exercise of sport-oriented physical education. Material and Methods: in the researches were involved 1-5 year basic department students of V. N Karazin Kharkov National University (n=36402). Methods: analysis of literature sources, formatted pedagogical experiment, sociological research, maths statistics. Results: through experimental research we found out that that usage of information communicative technologies in authors' model of sport-oriented physical education in high schools had provided increase in amount of students, who engaged in chosen sports (moving activity), by 14,4% (1463 persons). Conclusion: the usage of information communicative technologies in educational process promoted increasing of student quantity in the sport-oriented groups